Analisis kepuasan dari perspektif tingkat kepentingan layanan jamaah ibadah umrah PT. Attin Tour Travel Jambi - M. Dede Riandy; Erida Erida; Ade Titi Nifita (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the level of satisfaction of the Jamaah with the Umrah services at PT. ATTIN Tour Travel Jambi. This thesis uses data analysis which is used in this research is a quantitative descriptive analysis of Importance Performance Analysis (IPA) with data processing carried out by Microsoft Excel Software and Product Statiscal moment Person (SPSS) 20 For Windows. The results showed that the overall level of satisfaction in the service attributes of PT ATTIN Jambi which can be seen from the congregational satisfaction index (CSI) of 72.16%, which means that the average level of customer satisfaction is satisfactory or above the standard (71% - 85%) , based on the results of the IPA analysis, the statements considered the most important by the congregation were